'On the very spot': In Defence of Battle. Issue 1 (2012) - Porter, Roy
Abstract : The battle of Hastings is the most famous battle in English history. Two recently published books have claimed that the traditional location of the battle, commemorated by Battle Abbey, is wrong and that the battle occurred elsewhere. This article reviews the historical sources for the battle's location and concludes that there is compelling evidence that Battle Abbey was indeed founded on the battlefield.